Patterns and Outcomes of Endovascular Therapy in Mild Stroke: A Florida-Puerto Rico Collaboration. Issue 8 (August 2019) - Asdaghi, Negar; Yavagal, Dileep R.; Wang, Kefeng; Mueller-Kronast, Nils; Bhatt, Nirav; Gardener, Hannah E.; Gutierrez, Carolina M.; Marulanda-Londoño, Erika; Koch, Sebastian; Dong, Chuanhui; Oluwole, Sophia A.; Hanel, Ricardo; et al.
Abstract : Background and Purpose—: We aimed to evaluate the current practice patterns, safety and outcomes of patients who receive endovascular therapy (EVT) having mild neurological symptoms. Methods—: From Jan 2010 to Jan 2018, 127, 794 ischemic stroke patients were enrolled in the Florida-Puerto Rico Stroke Registry. Patients presenting within 24 hours of symptoms who received EVT were classified into mild (National Institutes of Health Stroke Scale [NIHSS] ⩽5) or moderate/severe (NIHSS>5) categories. Differences in clinical characteristics and outcomes were evaluated using multivariable logistic regression. Results—: Among 4110 EVT patients (median age, 73 [interquartile range=20] years; 50% women), 446 (11%) had NIHSS ⩽5. Compared with NIHSS >5, those with NIHSS ⩽5 arrived later to the hospital (median, 138 versus 101 minutes), were less likely to receive intravenous alteplase (30% versus 43%), had a longer door-to-puncture time (median, 167 versus 115 minutes) and more likely treated in South Florida (64% versus 53%). In multivariable analysis younger age, private insurance (versus Medicare), history of hypertension, prior independent ambulation and hospital size were independent characteristics associated with NIHSS ⩽5. Among EVT patients with NIHSS ⩽5, 76% were discharged home/rehabilitation and 64% were able to ambulate independently at discharge as compared with 53% and 32% of patients with NIHSS >5. Symptomatic intracerebral hemorrhage occurred in 4% of mild stroke EVT patients and 6.4% in those with NIHSS >5. Conclusions—: Despite lack of evidence-based recommendations, 11% of patients receiving EVT in clinical practice have mild neurological presentations. Individual, hospital and geographic disparities are observed among endovascularly treated patients based on the severity of clinical symptoms. Our data suggest safety and overall favorable outcomes for EVT patients with mild stroke. Abstract : Supplemental Digital Content is available in the text.